Differential effects of the early and late intrauterine environment on corticotrophic cell development - Timothy G. Butler; Jeff Schwartz; I. Caroline McMillen (The Journal of Clinical Investigation, 2002)
The developing embryo and fetus respond to a range of intrauterine stressors, but the effect of chronic intrauterine stress on the programmed development of pituitary corticotrophs has not been investigated. We have used a pregnant sheep model in which the embryonic environment at conception has been surgically perturbed by uterine carunclectomy. This procedure results in the development of fetuses that either are placentally restricted and chronically hypoxemic or that demonstrate compensatory placental growth and maintain normoxemia throughout late gestation. We found that uterine carunclectomy resulted in the emergence of a population of non–corticotrophin-releasing hormone (non-CRH) target cells that secreted high amounts of adrenocorticotrophic hormone (ACTH) in the fetal pituitary. This change in corticotroph development was independent of late-gestation hypoxemia. However, chronic hypoxemia during late gestation (in either carunclectomized or non-carunclectomized uterine environments) resulted in a reduction in the proportion of ACTH stored in CRH-target. Thus, the early and late intrauterine environments differentially program the development of specific corticotrophic cell types in the fetal pituitary. These patterns of altered corticotroph development are important given the central roles of the hypothalamo-pituitary-adrenal axis in the fetal adaptive response to intrauterine stress and in the early programming of adult disease.